2013
DOI: 10.1111/j.1601-5215.2012.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention for conversion disorder: neurologists and psychiatrists working together

Abstract: Early intervention involving both neurologists and psychiatrists is effective for CD in alleviating physical complaints, reducing sick leave and health care use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Of interest, a significant number of patients accepted psychiatric referral in our study, independently of the group allocation. This finding is in concordance with results of our retrospective study where 73%-83% of patients with conversion disorder accepted psychiatric referral [25]. It must be pointed out that both groups benefited from meetings with the psychiatrist and the neurologist for the diagnosis restitution (which is standard care in our center since 2005) and the 2-, 6-and 12-month evaluations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Of interest, a significant number of patients accepted psychiatric referral in our study, independently of the group allocation. This finding is in concordance with results of our retrospective study where 73%-83% of patients with conversion disorder accepted psychiatric referral [25]. It must be pointed out that both groups benefited from meetings with the psychiatrist and the neurologist for the diagnosis restitution (which is standard care in our center since 2005) and the 2-, 6-and 12-month evaluations.…”
Section: Discussionsupporting
confidence: 94%
“…The evidence of an association between childhood trauma and conversion disorder being meanwhile strong [23,24], we integrated basic psychotraumatology principles in our psychotherapeutic intervention, hoping to increase patients' treatment adherence. A retrospective study showed that such early intervention involving both neurologists and psychiatrists was effective in reducing physical symptoms, sick leave and health care use [25]. There are only very few published data on the efficacy of therapeutic interventions for conversion disorders [26].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments can include early intervention with neurology and psychiatry working together [15], focusing on specific symptoms such as cognitive behavioural therapy (CBT) for dissociative episodes [14,16], physiotherapy for functional movement disorders [17,18] or 1-week multidisciplinary (MDT) programmes for functional movement disorders (physical, occupational, psychotherapy, SALT) [19,20]. More complex and heterogenous symptom presentations often with co-morbidities and high levels of disability, have been referred to MDT (multidisciplinary team)-based programmes which have been delivered in inpatient neuropsychiatric settings [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric evaluation is important, as many FMD patients also suffer from psychiatric comorbidities such as anxiety and/or depression, but often only accepted with a good alliance with the patient [93].…”
Section: Treatment and Outcomementioning
confidence: 99%